White Privilege in Times of War: Media Narratives of the Conflict in Ukraine: Media Narratives of the Conflict in Ukraine - Altam, Saleh; G. D.Kokane, Dr. (South Asian Journal of Social Sciences and Humanities, 2023)
The purpose of this article is to shed light on the media coverage of the initial stages of the Russian invasion of Ukraine. The Western media’s reporting on the conflict was marked by biased and discriminatory comments. The Ukrainian refugees who fled to neighboring countries were compared unfavorably to refugees from other war-torn countries, based on superficial and irrelevant criteria such as skin color, religion, race, and qualifications, rather than on the basis of their human suffering. The European media coverage normalized conflicts in other parts of the world, particularly in the Middle East, portraying them as expected and commonplace. Conversely, conflicts occurring in Europe are deemed shameful for humanity, and white individuals are seen as unsuitable for becoming refugees. Additionally, the article examines the broader war scenario, suggesting that the current conflict may lead the world towards a third world war, due to the escalating tension between Russia and Western powers. The conflict may be geographically centered in Ukraine, but it is essentially a battle between Russia and Ukraine, with backing from the United States and Europe. This conflict has also had ripple effects on other nations, as tensions have risen between China and Taiwan, North Korea and Japan, and Kosovo and Serbia.